A Matter of Scale. Issue 1 (20th April 2020) - Chen, Wang‐Ping
Abstract: Plate tectonics, one of the greatest scientific discoveries of the twentieth century, works particularly well in oceanic regions but has considerable difficulty to account for widespread, diffuse deformation of the continents. There has been an enduring discourse on whether continuous deformation of the crust or slip along discrete faults is a better approximation of continental tectonics. A key difficulty in resolving this issue is that the distinction between flow and slip is scale dependent. Moreover, even at scales of tens of millimeters or less, both mechanisms of deformation can coexist. Over times much longer than about 100 years, the limit of reliable geophysical data, the scale in time further complicates the problem of spatial scales. However, solutions to some problems in continental tectonics do not rely on end‐member models, and advances in understanding the role of the lithospheric mantle beneath the continental crust point the need to extend our focus below the crust. Plain Language Summary: In the aftermath of plate tectonics, one of the greatest scientific discoveries of the twentieth century, the nature of widespread, diffuse deformation of the continents has been on the leading edge of research for over 50 years. This issue is also of great societal impact as many of the most devastating continental earthquakes occur away from boundaries of tectonic plates. I trace how two contrasting concepts on this subject developed and conclude that scales in space and in time are keys to understanding deformation of the continental crust. Key Points: Plate tectonics, a great scientific discovery of all times, explains the deformation of oceanic regions well but not that of continents The distinction between flow and slip is scale dependent, and both can coexist even at small spatial scales Recent advances point to the importance of understanding the role of the lithospheric mantle in continental tectonics